Working in a cold environment, feeling cold at work and chronic pain: a cross-sectional analysis of the Tromsø Study - Farbu, Erlend Hoftun; Skandfer, Morten; Nielsen, Christopher Sivert; Brenn, Tormod; Stubhaug, Audun; Höper, Anje Christina (BMJ Open, 2019)
Aim - The aim of this study was to investigate if working in a cold environment and feeling cold at work are associated with chronic pain (ie, lasting ≥3 months). Methods - We used data from the sixth survey (2007–2008) of the Tromsø Study. Analyses included 6533 men and women aged 30–67 years who were not retired, not receiving full-time disability benefits and had no missing values. Associations between working in a cold environment, feeling cold at work and self-reported chronic pain were examined with logistic regression adjusted for age, sex, education, body mass index, insomnia, physical activity at work, leisure time physical activity and smoking. Results - 779 participants reported working in a cold environment ≥25% of the time. This exposure was positively associated with pain at ≥3 sites (OR 1.57; 95% CI 1.23 to 2.01) and with neck, shoulder and leg pain, but not with pain at 1–2 sites. Feeling cold sometimes or often at work was associated with pain at ≥3 sites (OR 1.58; 95% CI 1.22 to 2.07 and OR 3.90; 95% CI 2.04 to 7.45, respectively). Feeling cold often at work was significantly and positively associated with pain at all sites except the hand, foot, stomach and head. Conclusion - Working in a cold environment was significantly associated with chronic pain. The observed association was strongest for pain at musculoskeletal sites and for those who often felt cold at work.